PENGARUH BOARD GENDER DIVERSITY, BOARD SIZE, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - Robby Krisyadi; Vivian vivian (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to research whether board gender diversity, board size and leverage have influences on tax avoidance. This research involves a purposive sampling method and obtains 1660 company data listed on the Indonesia Stock Exchange (IDX) that met the sample criteria for the period 2017-2021. The results showed that tax avoidance in Indonesia do not influence board size, board gender diversity and leverage.